The Protester, the Dissident and the Christian - Johnson, Thomas K. (Evangelical review of theology, 2020)
When and why should Christians protest? How can we turn the hearts of other protesters towards the hope offered by the Christian gospel? This article, revised from a sermon originally preached during the Arab Spring uprisings, answers those timely questions as we experience another year of widespread protests.